Preoperative SCC-Ag as a predictive marker for the use of adjuvant chemotherapy in cervical squamous cell carcinoma with intermediate-risk factors - Guo, Hong-tao (BMC Cancer, 2020)
BACKGROUND: For cervical cancer patients whose tumors display a combination of intermediate risk factors, postoperative radiation with or without adjuvant chemotherapy is suggested for them. However, who should be administered with adjuvant chemotherapy is unknown. The current study was designed to explore the clinical value of squamous cell carcinoma antigen (SCC-Ag) in guiding the use of adjuvant chemotherapy in cervical cancer patients. METHODS: A total of 301 cervical cancer patients were included in the present study from March 2006 to March 2016. There were 156 patents who received adjuvant chemotherapy, while the rest of 145 patents did not receive it. The survival analysis including Overall survival (OS) and disease-free survival (DFS) was assessed by using the Kaplan-Meier method. Cox proportional hazards regression was done to detect factors in predicting the tumor prognosis. RESULTS: In patients with high pre-treatment SCC-Ag level, those who received adjuvant chemotherapy acquired better prognosis than patients who did not receive it. Particularly, a lower rate of distant metastasis was found in the group of adjuvant chemo-radiotherapy than that in the group of adjuvant radiotherapy. As for patients with low pre-treatment SCC-Ag level, we observed no differences in both the OS and DFS between patients who were given and not given with adjuvant chemotherapy. In the multivariable analysis, adjuvant chemotherapy was significantly correlated with DFS and distant metastasis-free survival (DMFS) in patients with high SCC-Ag level. CONCLUSION: Preoperative SCC-Ag can be a predictive marker for the use of adjuvant chemotherapy in cervical squamous cell carcinoma with intermediate-risk factors.